(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This article examines questions related to the repercussions that compulsory expropriations have on taxes, which have been controversial in the light of recentcourt rulings which have set judicial precedents and administrative doctrine. Taking the provisions in Article 49 of the Spanish Compulsory Expropriation Act as a pointof departure, the existing relationship between the constitutional guarantees establishedin Article 33 of the EC and taxation is analysed. In addition, aspects of bothindirect and direct taxation which have been controversial and led to judicial judgments and rulings by the Economic and Administrative Courts or the Directorate General of Taxation, are discussed.